Application of a WeChat-based mini-app as a patient reminder in Helicobacter pylori eradication: a prospective multi-center randomized controlled study - Kefang Sun; Yishu Chen; Zhenzhen Wang; Yi Liu; Yue Pan; Xinli Mao; Lei Xu; Chaohui Jin; Ming Chen; Chaohui Yu; Lan Li (BMC Gastroenterology, 2022)
Abstract Background To improve the eradication rate of H. pylori, researchers have investigated the role of WeChat-based mini-app as an electronic reminding system in H. pylori treatment. Methods Subjects from three medical centers were divided into two groups. Patients in the daily mini-app-based notification system group received daily notifications via the WeChat mini-app. Patients in the control group received one-time verbal education on the first clinical visit. Both groups received a 14-day quadruple therapy to eradicate H. pylori infection. Eradication rate, compliance, adverse events and satisfaction were evaluated. Results Both intention-to-treat (ITT) and per-protocol (PP) analyses were conducted. The eradication rate in the daily mini-app-based notification system group was slightly higher compared with the control group (ITT analysis: 76.70% vs. 70.73%, p = 0.312; PP analysis: 85.87% vs. 82.86%, p = 0.562). The compliance was significantly higher in the daily mini-app-based notification system group (ITT analysis: 85.52% vs. 70.48%, p = 0.028; PP analysis: 92.39% vs. 81.90%, p = 0.030). The adverse event rates were similar between the two groups (PP analysis: 36.96% vs. 40.95%, p = 0.566). No significant difference in eradication rate was seen in each subgroup analysis by age, place of residence, grade of education, or endoscopic findings. Conclusion The study showed that daily mini-app-based notification improved patient compliance but not H. pylori eradication rate. Trial registration The research was registered in the Chinese Clinical Trial Registry (ChiCTR2000031011, 21/03/2020).